2000
DOI: 10.1136/jcp.53.2.140
|View full text |Cite
|
Sign up to set email alerts
|

A study of interval breast cancer within the NHS breast screening programme

Abstract: Aim-To define the biological nature and malignant potential of interval cancers presenting to a breast unit within the NHS breast screening programme. Methods-112 interval cancers were compared with matched, screen detected and symptomatic cancers in terms of their radiographic, histopathological, and immunohistochemical features. Results-Interval cancers, strictly defined, showed no characteristic radiographic pattern. In terms of size, vascular invasion, lymph node status, and prognosis they were intermediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
35
3
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 38 publications
(34 reference statements)
13
35
3
1
Order By: Relevance
“…Furthermore, loss of TP53 function eliminates the growth arrest response to DNA damage and impairs the apoptotic programme. Consequently, tumors with TP53 mutations may have a higher frequency of mutations in other genes and this might also contribute to explain the higher proliferative rate of interval cancers (1,7,8,43), as found in the present study.…”
Section: Discussionsupporting
confidence: 69%
“…Furthermore, loss of TP53 function eliminates the growth arrest response to DNA damage and impairs the apoptotic programme. Consequently, tumors with TP53 mutations may have a higher frequency of mutations in other genes and this might also contribute to explain the higher proliferative rate of interval cancers (1,7,8,43), as found in the present study.…”
Section: Discussionsupporting
confidence: 69%
“…In addition, another study showed that 13% of women with a palpable breast mass and a diagnosis of invasive cancer had had a normal mammogram within the preceding year 36 . Interval cancers often show aggressive features 37 , and it is not impossible that some of the cancers detected by cbe alone in the present study were interval cancers. Triple-negative cancers are often found in BRCA mutation carriers, but according to a systematic review 38 , the exact value of cbe for hereditary cancers might be controversial.…”
Section: Figurementioning
confidence: 84%
“…There is consensus that interval breast cancers have a lessfavorable prognosis than screen-detected cancers [6][7][8][9][10]. A delay in diagnosis could potentially worsen prognosis and consequently impair the efficiency of the screening program.…”
Section: Introductionmentioning
confidence: 98%